PERAN STAKEHOLDER PENTAHELIX MELALUI CORPORATE SOCIAL RESPONSIBILITY DALAM MENEKAN TINGKAT PENGANGGURAN PADA MASYARAKAT LOKAL - Reza Aulia Kartika Indrawati (Tourism Department, State Polytechnic of Banyuwangi, 2024)
This study aims to analyze the implementation of the role of pentahelix stakeholders in Kemiren Tourism Village homestays through corporate social responsibilities (CSR) in reducing the unemployment rate. This research uses a qualitative method that collects data through observation, document study, and interviews with pokdarwis, Keboundha media, Village Head, Lecturers and Students, local communities, staff, and or homestay owners. The results showed that CSR programs manifested in skills training, tourism promotion, homestay infrastructure development, and policymaking have succeeded in increasing income and reducing unemployment rates in Kemiren Tourism Village. The success of these programs is largely due to the active role of Pentahelix stakeholders, including government, business people, academics, community, and media. The findings show that stakeholders work well together in supporting CSR programs to create jobs and improve the local economy, decreasing the unemployment rate in Kemiren Tourism Village. It also helps the government and businesses in planning and realizing sustainable CSR programs to improve community welfare supported by the readiness of local communities to reduce unemployment